Cerebral function in posttraumatic stress disorder during verbal working memory updating: a positron emission tomography study - Clark, C.Richard; McFarlane, Alexander C; Morris, Philip; Weber, Darren L; Sonkkilla, Cynon; Shaw, Marnie; Marcina, Jackie; Tochon-Danguy, H.J; Egan, Gary F (Biological psychiatry (1969), 2003)
This study examined cerebral function in posttraumatic stress disorder (PTSD) during the updating of working memory to trauma-neutral, verbal information. Ten PTSD and matched control subjects completed a visuoverbal target detection task involving continuous updating (Variable target condition) or no updating (Fixed target condition) of target identity, with updating activity estimated by condition comparison. Normal updating activity using this paradigm involved bilateral activation of the dorsolateral prefrontal cortex (DLPFC) and inferior parietal lobe. The PTSD group lacked this activation in the left hemisphere and was significantly different from control subjects in this regard, but showed additional activation in the superior parietal lobe, bilaterally. The pattern of parietal activation suggests a dependence on visuospatial coding for working memory representation of trauma-neutral, verbal information. Group differences in the relative involvement of the DLPFC indicate less dependence in PTSD on the executive role normally attributed to the left DLPFC for monitoring and manipulation of working memory content in posterior regions of the brain.